Folic acid deficiency declined substantially after introduction of the mandatory fortification programme in Queensland, Australia: a secondary health data analysis. Issue 18 (4th September 2019) - Slagman, Anna; Harriss, Linton; Campbell, Sandra; Muller, Reinhold; McDermott, Robyn
Abstract: Objective: To investigate the prevalence of folic acid deficiency in Queensland-wide data of routine laboratory measurements, especially in high-risk sub-populations. Design: Secondary health data analysis. Setting: Analysis of routine folic acid tests conducted by Pathology Queensland (AUSLAB). Participants: Female and male persons aged 0–117 years with routine folic acid testing between 1 January 2004 and 31 December 2015. If repeat tests on the same person were conducted, only the initial test was analysed ( n 291 908). Results: Overall the prevalence of folic acid deficiency declined from 7·5 % before (2004–2008) to 1·1 % after mandatory folic acid fortification (2010–2015; P < 0·001) reflecting a relative reduction of 85 %. Levels of erythrocyte folate increased significantly from a median (interquartile range) of 820 (580–1180) nmol/l in 2008 before fortification to 1020 (780–1350) nmol/l in 2010 ( P < 0·001) after fortification. The prevalence of folic acid deficiency in the Indigenous population (14 792 samples) declined by 93 % (17·4 v . 1·3 %; P < 0·001); and by 84 % in non-Indigenous residents (7·0 v . 1·1 %; P < 0·001). In a logistic regression model the observed decrease of folic acid deficiency between 2008 and 2010 was found independent of gender, age and ethnicity (ORcrude = 0·20; 95 % CI 0·18, 0·23; P < 0·001; ORadjusted = 0·21; 95 % CI 0·18, 0·23; P < 0·001). Conclusions: While voluntary folic acid fortification, introduced in 1995, failed especially in high-risk subgroups, the 2009 mandatory folic acid fortification programme coincided with a substantial decrease of folic acid deficiency in the entire population.